2020
DOI: 10.1136/bmjgh-2020-003328
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of ‘safe’ water: the burden of personal injury from water fetching in 21 low-income and middle-income countries

Abstract: IntroductionWater fetching for household needs can cause injury, but documentation of the burden of harm globally has been limited. We described the frequency, characteristics and correlates of water-fetching injuries in 24 sites in 21 low-income and middle-income countries in Asia, Africa and Latin America and the Caribbean.MethodsIn a survey of 6291 randomly selected households, respondents reported whether and how they had experienced water-fetching injuries. Responses were coded for injury type, mechanism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 31 publications
(44 reference statements)
2
39
0
Order By: Relevance
“…Interestingly, higher functioning in daily activities was found for women carrying downhill. These findings align with previous studies that showed that certain terrains can put an added risk to physical health [7]. Beyond previous results, our study showed that terrain also moderates the relationship between physical burden and psychosocial well-being.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Interestingly, higher functioning in daily activities was found for women carrying downhill. These findings align with previous studies that showed that certain terrains can put an added risk to physical health [7]. Beyond previous results, our study showed that terrain also moderates the relationship between physical burden and psychosocial well-being.…”
Section: Discussionsupporting
confidence: 93%
“…In 2017, 25% of the global population collected water from sources that are located off premises [2]. Previous research on the health consequences of sub-optimal water access has described adverse impacts of low water quality [3,4], the transport of water [5][6][7] water insecurity [8,9], and poor menstrual hygiene management [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical distancing guidelines would also seemingly discourage water fetching in groups, which eliminates a way of maintaining social capital and an important safety buffer for women and children, who frequently suffer harassment, assault, and accidents while fetching water throughout the world ( Collins et al, 2019 ; Venkataramanan et al, 2020 ). This reality can shape water-related decision making and cause women to take risks, such as using alternative inferior sources or navigating physically dangerous terrain to obtain water elsewhere ( Smiley and Stoler, 2020 ).…”
Section: Resultsmentioning
confidence: 99%